Chinese ways of seeing and open-air painting - Gu, Yi (Harvard East Asian monographs, 2020)
How did modern Chinese painters see landscape? Did they depict nature in the same way as premodern Chinese painters? What does the artistic perception of modern Chinese painters reveal about the relationship between artists and the nation-state? Could an understanding of modern Chinese landscape painting tell us something previously unknown about art, political change, and the epistemological and sensory regime of twentieth-century China? Yi Gu tackles these questions by focusing on the rise of open-air painting in modern China. Chinese artists almost never painted outdoors until the late 1910s, when the New Culture Movement prompted them to embrace direct observation, linear perspective, and a conception of vision based on Cartesian optics. The new landscape practice brought with it unprecedented emphasis on perception and redefined artistic expertise. Central to the pursuit of open-air painting from the late 1910s right through to the early 1960s was a reinvigorated and ever-growing urgency to see suitably as a Chinese and to see the Chinese homeland correctly. Examining this long-overlooked ocular turn, Gu not only provides an innovative perspective from which to reflect on complicated interactions of the global and local in China, but also calls for rethinking the nature of visual modernity there